Motivasi Kerja Sebagai Mediasi Pengaruh Lingkungan dan Disiplin Terhadap Kinerja Karyawan - Nurwati Nurwati (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
This study aims to analyze various factors that influence employee performance at Coffee Coftea Kendari. Specifically, this study examines (1) the influence of the work environment on employee performance, (2) the influence of work discipline on employee performance, (3) the influence of the work environment on employee performance, (4) the influence of work discipline on employee performance, (5) the influence of work motivation on employee performance, (6) the influence of the work environment on employee performance through work motivation, and (7) the influence of work discipline on employee performance. The results of the study indicate that the work environment has a positive and significant effect on employee performance at Coffee Coftea Kendari. This means that the better the work environment provided, the higher the employee performance. However, the work environment does not have a significant effect on work motivation. This shows that although a comfortable work environment can improve performance, work motivation factors are more influenced by other variables, such as work discipline. Work discipline has been shown to have a positive and significant effect on work motivation and employee performance. This shows that employees who have high work discipline tend to have a stronger motivation to work well, which in turn improves their performance. Work motivation was also found to have a positive and significant influence on employee performance, confirming that high motivation can encourage employees to improve their productivity and work quality. Furthermore, this study also found that work motivation only significantly mediated the effect of work discipline on employee performance, but did not mediate the effect of the work environment on employee performance. This means that although work motivation plays an important role in improving performance influenced by work discipline, motivation does not act as a mediator linking the work environment to employee performance.